In vitro cytotoxicity studies of parent and nanoencapsulated Holmium-2, 9-dimethyl-1, 10-phenanthroline complex toward fish-salmon DNA-binding properties and antibacterial activity. Issue 17 (22nd November 2019) - Jahani, Shohreh; Noroozifar, Meissam; Khorasani-Motlagh, Mozhgan; Torkzadeh-Mahani, Masoud; Adeli-Sardou, Mahboubeh
Abstract: In this study, the interaction of Holmium (Ho) complex including 2, 9-dimethyl-1, 10-phenanthroline, also called Neocuproine (Neo), [Ho(Neo)2 Cl3 .H2 O], as fluorescence probe with fish-salmon DNA (FS-DNA) is studied during experimental investigations. Multi-spectroscopic methods are utilized to determine the affinity binding constants ( K b ) of complex–FS-DNA. It is found that fluorescence of Ho complex is strongly quenched by the FS-DNA through a static quenching procedure. Under optimal conditions in Tris(trishydroxymethyl-aminomethane)–HCl buffer at 25 °C with pH ≈ 7.2, intrinsic binding constant K b of Ho complex is 6.12 ± 0.04 × 10 5 M −1 . Also, the binding site number and Stern–Volmer quenching constant are calculated. There are different approaches, including iodide quenching assay, salt effect and thermodynamical assessment to determine the features of the binding mode between Ho complex and FS-DNA. Also, the parent and starch and lipid nanoencapsulated Ho complex, as potent antitumor candidates, were synthesized. The main structure of Ho complex is maintained after encapsulation using starch and lipid nanoparticles. 3-[4, 5-Dimethylthiazole-2-yl]-2, 5-diphenyltetrazolium bromide (MTT) method was used to assess the anticancer properties of Ho complex and its encapsulated forms on human cancer cell lines of human lung carcinoma cell line and breast cancer cell line. In conclusion, these compounds could be considered as new antitumor candidates. Communicated by Ramaswamy H. Sarma